PtCo intermetallic compound and preparation method and application thereof
By loading the Pt-Co bimetallic complex on the carbon support and performing high-temperature heat treatment, the problem of difficult control of the size and ordering degree of Pt-based intermetallic compounds in the prior art is solved, and a small particle size, high activity and high durability PtM-IMC catalyst is realized, which significantly improves the ORR catalytic performance.
Patent Information
- Application Number
- CN202411679459.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to accurately control the size, composition uniformity and atomic ordering of Pt-based intermetallic compounds on carbon support, resulting in insufficient activity and stability of the catalyst.
Small-sized and highly active Pt1Co1 intermetallic nanoparticles were directly obtained by loading the crystals of the precisely constructed Pt-Co bimetallic complex salt on a carbon support and heat treatment at high temperatures.
The synthesis of PtM-IMC catalysts with small particle size and high order degree was achieved, which significantly improved ORR catalytic activity and durability, increased mass activity by 2.5 times, and the activity attenuation after durability test was about 31%.
Smart Images

Figure CN119650717A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cell catalysts, and in particular relates to a PtCo intermetallic compound and a preparation method and application thereof. Background Art
[0002] Since the cathode oxygen reduction reaction (ORR) of PEMFCs (Proton Exchange Membrane Fuel Cells, PEMFCs) is a relatively complex reaction process involving multi-electron transfer, the kinetics are relatively slow, and a suitable catalyst is usually required to improve the kinetics of the reaction. In recent years, a new type of ORR catalyst has emerged: ordered intermetallic compounds (IMCs). Unlike disordered solid solution alloys, the atoms in ordered intermetallic compounds are arranged in an orderly manner, showing a higher mixing enthalpy. Pt and transition metal M occupy specific lattice sites respectively, and Pt (5d) and M (3d) orbits are strongly coupled, which can effectively alleviate the dissolution and loss of M in the electrochemical process, thereby improving the activity and stability of the catalyst. However, it is quite difficult to accurately control the size, uniformity of composition and degree of atomic ordering of Pt-based intermetallic compounds on carbon supports. Therefore, how to directly and efficiently prepare PtM-IMC catalysts with high degree of ordering and small particle size is a key scientific and technological problem that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a simple method for directly synthesizing a small-sized, highly active PtM intermetallic compound catalyst on a carbon support, and to study its application in the ORR catalytic process, so as to provide a new solution strategy for developing a new type of highly active and durable fuel cell cathode PtM intermetallic compound catalyst. Based on this, the first aspect of the present invention provides a method for preparing a PtCo intermetallic compound, comprising the following steps:
[0004] 1) [Co(NH 3 ) 5 Cl]Cl 2 Dissolve in water, add carbon powder, disperse by ultrasonication, and stir overnight to obtain solution A; dissolve potassium chloroplatinite in water to obtain solution B;
[0005] 2) adding the solution B dropwise to the solution A and stirring to react, filtering and drying after the reaction is completed to obtain a precursor mixture;
[0006] 3) heating the precursor mixture in a reducing atmosphere for 2 h to 6 h at a heating temperature of 600° C. to 900° C., and then naturally cooling to room temperature to obtain a target powder;
[0007] 4) washing the target powder in an acid solution, washing with water, and drying to obtain the PtCo intermetallic compound.
[0008] The present invention starts from the source of synthesizing intermetallic compounds. By loading the precisely constructed Pt-Co bimetallic complex salt crystals on a carbon carrier, small-sized and highly active Pt1Co1 intermetallic compound nanoparticles can be directly obtained through high-temperature heat treatment. In this method, a [Co(NH 3 ) 5 Cl][PtCl 4 ] bimetallic complex salt crystals, composed of [Co(NH 3 ) 5 Cl] 2+ Cations and [PtCl 4 ] 2- Anion composition, thus two different metals can be directly anchored in one molecule on the carbon support, and then small-sized Pt1Co1 intermetallic compound nanoparticles can be obtained by high-temperature pyrolysis. Coupling Pt and Co atoms in one molecule greatly shortens the diffusion distance between atoms, which is conducive to ordering during high-temperature annealing, thereby realizing the synthesis of small-particle size, highly ordered catalysts.
[0009] In some implementations, in the above step 1), the above carbon powder may be commercial carbon powder such as C-72, EC-300, KB-600 or BP-2000; after adding the above carbon powder, ultrasonication is required to ensure that it is evenly dispersed, and then stirring is continued overnight (at room temperature) to ensure that the carbon powder and [Co(NH 3 ) 5 Cl]Cl 2 Mix thoroughly and evenly; the ultrasonic time is 0.5h-2h.
[0010] In some implementations, in the above step 2), a KDS syringe pump can be used to drip the above solution B; the dripping rate is 2mL / h-15mL / h, and the stirring rate is 400rpm-1200rpm; after the above solution B is dripped, stirring is continued for 5h-12h, the purpose is to make the two different metal ions fully react and completely deposit on the carbon carrier (i.e., the above carbon powder) to avoid metal loss; wherein the potassium chloroplatinate in the above solution B and the [Co(NH 3 ) 5 Cl]Cl 2 The molar ratio is 1:(1-2).
[0011] After the reaction in the above step 2) is completed, the reaction system (i.e., the mixed solution after the reaction is completed) is filtered (the filtrate is colorless, indicating that all the metals are adsorbed on the carbon carrier), and then the obtained filter cake is placed in a vacuum oven for drying to obtain a powder of the above precursor mixture; wherein the drying temperature is 55°C-80°C, and the drying time is 12h-24h.
[0012] In some implementations, in the above step 3), the above precursor mixture is placed in a reducing atmosphere, and the temperature is raised to 600°C-900°C at a heating rate of 5°C / min-10°C / min, and maintained for 2h-6h; thereby achieving PtM alloy and ordering. Wherein, the above reducing atmosphere includes hydrogen and argon; in the specific implementation process, the above precursor mixture is placed in a tubular furnace for the above heating treatment, and before the above heating treatment / heating stage, a vacuum ventilation operation (at least 3 times) is performed to completely remove the air in the tubular furnace to ensure that the above heating treatment is carried out in the above reducing atmosphere; at this time, the flow rates of hydrogen and argon are both controlled to be 200sccm-500sccm.
[0013] In some implementations, in the above step 4), the specific washing process includes: ultrasonically dispersing the above target powder in the above acid solution, and stirring at 55°C-85°C for 4h-12h; the purpose is to remove unstable metal ions and anions therein. The above acid solution is an aqueous solution of sulfuric acid, nitric acid, hydrochloric acid or perchloric acid, and the concentration of the above acid solution is 0.1M-5M; after washing with the above acid solution, suction filtration is performed, and the obtained filter cake is washed with water until the washing liquid is neutral, and then dried; the drying temperature is 55°C-80°C, and the drying time is 12h-24h; in addition, the final PtCo intermetallic compound can be ground according to actual needs.
[0014] The second aspect of the present invention provides a PtCo intermetallic compound prepared by the above preparation method, which can be used as a catalyst in the field of fuel cell ORR. After continuous optimization of the synthesis conditions, the final PtM-IMC catalyst showed ORR catalytic activity superior to that of commercial Pt / C, especially the mass activity was increased by 2.5 times; in addition, it also performed outstandingly in terms of durability, and the mass activity decayed by about 31% after 10,000 cycles of accelerated durability testing; at the same time, it also showed extremely high performance in fuel cell tests, H 2 -air and H 2 -O 2 Under these conditions, the power density of the battery can reach 1.06 / 2.13Wc m -2 , and at 1A cm -2 The battery voltage shows almost no decay when discharged for 100h at a constant current density.
[0015] The beneficial effects of the present invention are as follows: starting from the source of synthesizing intermetallic compounds, the present invention loads precisely constructed Pt-Co bimetallic complex salt crystals on a carbon carrier, and then directly obtains small-sized, highly active Pt1Co1 intermetallic compound nanoparticles after high-temperature heat treatment; the final PtM-IMC catalyst exhibits ORR catalytic activity superior to that of commercial Pt / C, especially a 2.5-fold increase in mass activity, and also outstanding performance in durability, while also exhibiting extremely high performance in fuel cell tests, providing an advanced synthesis strategy for the preparation of future new generation fuel cell ORR catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Shown are X-ray diffraction patterns of pure metal Pt and the Pt1Co1-IMC / C catalyst prepared in Example 1;
[0017] Figure 2 Shown are the morphology (a), particle size distribution (b), high-resolution electron microscopy (c), spherical aberration electron microscopy (d) and elemental analysis diagram (e) of the Pt1Co1-IMC / C catalyst prepared in Example 1;
[0018] Figure 3 Shown are the X-ray electron spectra of Pt / C and Pt1Co1-IMC / C samples in the Pt 4f binding energy region;
[0019] Figure 4 Shown are the CV curves, ORR polarization curves, and comparison graphs of mass activity and area specific activity of Pt1Co1-IMC / C and comparative Pt / C catalysts; wherein, (a) is the CV curves of Pt1Co1-IMC / C and Pt / C catalysts; (b) is the ORR polarization curves of Pt1Co1-IMC / C and Pt / C catalysts; (c) is a comparison graph of mass activity and specific activity of Pt1Co1-IMC / C and Pt / C catalysts;
[0020] Figure 5 Shown are (a) cyclic voltammetry curves of the Pt1Co1-IMC / C catalyst before and after 10,000 cycles; (b) polarization curves; (c) changes in mass specific activity; (d) changes in area specific activity;
[0021] Figure 6 The results show that Pt1Co1-IMC / C and Pt / C in H 2 –air and H 2 –O 2 Steady-state polarization curves in fuel cells (a, b) and Pt1Co1-IMC / C catalyst in H 2-air stability test (c), and performance comparison with some materials published in the literature (d). DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0023] Example 1
[0024] A PtCo intermetallic compound (Pt1Co1-IMC / C catalyst), the preparation method of which comprises the following steps:
[0025] 1) Weigh 0.0493 g of [Co(NH 3 ) 5 Cl]Cl 2 The powder was placed in a 250 mL beaker, 100 mL of deionized water was added, and magnetic stirring was performed for 1 h to fully dissolve the solution until it was clear. Then 0.2 g of XC-72 powder was weighed and added to the clear solution, and ultrasonic dispersion was performed for 30 min to make it dispersed sufficiently uniformly and stirred at room temperature overnight to make [Co(NH 3 ) 5 Cl]Cl 2 Mix thoroughly with XC-72 carbon powder to obtain solution A;
[0026] Weigh 0.0899 g of potassium chloroplatinite particles and dissolve them in 20 mL of deionized water, stirring them magnetically to completely dissolve them, to obtain solution B;
[0027] 2) At room temperature, solution B was slowly added to solution A at a rate of 5 mL / h using a KDS syringe pump under magnetic stirring (i.e., [Co(NH 3 ) 5 Cl]Cl 2 and carbon powder mixed solution), so that [Co(NH 3 ) 5 Cl] 2+ Cations and [PtCl 4 ] 2- The anions reacted and deposited on the carbon support, the molar ratio of metal Pt and Co was 1:1.1, and the mixture was stirred at room temperature for 9.5 hours. The mixture was filtered and the filtrate was colorless, indicating that the two metal ions reacted and were completely deposited on the carbon support. The filter cake was placed in a vacuum oven at 60°C and dried for 12 hours to obtain a precursor mixture.
[0028] 3) placing the above precursor mixture in a porcelain boat and slowly placing it into a tube furnace for direct high-temperature heat treatment, performing a vacuum ventilation operation before the heating stage to completely remove the air in the tube furnace to ensure a reducing atmosphere, and then heating according to the set program, specifically as follows: heating to 650°C at a heating rate of 5°C / min, keeping the temperature for 2.5h, then naturally cooling to room temperature, opening the lid, and taking out the black powder sample after high-temperature heat treatment;
[0029] 4) The cooled black powder sample was ultrasonically dispersed in 0.5 MH 2 SO 4 The solution was heated for 4 hours for acid washing, and the temperature was set to 65°C to remove unstable transition metal Co ions and anions; ultrapure water was used for washing 3 times by suction filtration until it was neutral, and then placed in a vacuum oven for drying until it was dried to finally obtain a PtCo intermetallic compound, namely, Pt1Co1-IMC / C catalyst powder.
[0030] in, Figure 1 : The X-ray diffraction diagram of pure metal Pt and the Pt1Co1-IMC / C catalyst prepared in this example. From the diagram, the superlattice diffraction peak of Pt1Co1 can be seen, indicating the formation of Pt1Co1 intermetallic compound. Figure 2 The morphology, particle size distribution, high-resolution electron microscopy, spherical aberration electron microscopy and elemental analysis of the Pt1Co1-IMC / C catalyst show that the average particle size of Pt1Co1-IMC is 4.25nm, and the particle size distribution is narrow. At the same time, the superlattice (111) of Pt1Co1-IMC is clearly visible, which once again proves the formation of intermetallic compounds. Elemental analysis shows that Pt and Co are evenly distributed, and no phase separation is found. Figure 3 4f is the X-ray electron spectrum of Pt / C and Pt1Co1-IMC / C samples in the Pt 4f binding energy region, which clearly shows that the Pt in the Pt1Co1-IMC / C catalyst prepared in this example is mainly in a metallic state.
[0031] Example 2
[0032] A PtCo intermetallic compound, the preparation method of which comprises the following steps:
[0033] 1) Weigh 0.0493 g of [Co(NH 3 ) 5 Cl]Cl 2 The powder was placed in a 250 mL beaker, 100 mL of deionized water was added, and magnetic stirring was performed for 1 h to fully dissolve the solution until it was clear. Then 0.2 g of XC-72 powder was weighed and added to the clear solution, and ultrasonic dispersion was performed for 30 min to make it dispersed sufficiently uniformly and stirred at room temperature overnight to make [Co(NH 3 ) 5Cl]Cl 2 Mix thoroughly with XC-72 carbon powder to obtain solution A;
[0034] Weigh 0.0899 g of potassium chloroplatinite particles and dissolve them in 20 mL of deionized water, stirring them magnetically to completely dissolve them, to obtain solution B;
[0035] 2) At room temperature, solution B was slowly added dropwise into solution A at a rate of 8 mL / h using a KDS syringe pump under magnetic stirring (i.e., [Co(NH 3 ) 5 Cl]Cl 2 and carbon powder mixed solution), so that [Co(NH 3 ) 5 Cl] 2+ Cations and [PtCl 4 ] 2- The anions reacted and deposited on the carbon support, the molar ratio of metal Pt and Co was 1:1.1, and the mixture was stirred at room temperature for 9.5 hours. The mixture was filtered and the filtrate was colorless, indicating that the two metal ions reacted and were completely deposited on the carbon support. The filter cake was placed in a vacuum oven at 60°C and dried for 12 hours to obtain a precursor mixture.
[0036] 3) placing the above precursor mixture in a porcelain boat and slowly placing it in a tube furnace for direct high-temperature heat treatment, performing a vacuum ventilation operation before the heating stage to completely remove the air in the tube furnace to ensure a reducing atmosphere, and then heating according to the set program, specifically as follows: heating to 800°C at a heating rate of 10°C / min, keeping the temperature for 2h, then naturally cooling to room temperature, opening the lid, and taking out the black powder sample after high-temperature heat treatment;
[0037] 4) The cooled black powder sample was ultrasonically dispersed in 0.5 MH 2 SO 4 The solution was heated for 4 hours for acid washing, and the temperature was set to 65°C to remove unstable transition metal Co ions and anions; ultrapure water was used for washing 3 times by suction filtration until it was neutral, and then placed in a vacuum oven for drying until it was dried to finally obtain a PtCo intermetallic compound.
[0038] Performance Experiment
[0039] (1) The Pt1Co1-IMC / C catalyst powder prepared in Example 1 was prepared into an electrochemical test ink solution. The specific formula of the ink solution is as follows: 2 mg of catalyst, 25 μL of 5% Nafion solution, and 975 μL of isopropanol. The prepared ink solution was then ultrasonically dispersed for 3 hours to ensure that it was evenly dispersed. The working electrode used in the test was a glassy carbon electrode (GC) with a diameter of 5 mm. The glassy carbon electrode was replaced with an Al2 O 3 Polishing powder is used to make it smooth and clean. 12.8 μL of ink solution is added to the previously polished GC and allowed to dry naturally at room temperature to make a working electrode for testing. At this time, the loading of precious metal Pt is 15 μg. Pt cm -2 .
[0040] Electrochemical performance test: The working electrode prepared using the Pt1Co1-IMC / C catalyst was tested for oxygen reduction performance. The specific steps are as follows: First, prepare fresh 0.1M HClO 4 solution, and then 0.1 M HClO 4 The solution was poured into a five-well electrolytic cell and N 2 The solution was saturated for half an hour to ensure that the oxygen in the electrolyte was removed. CV and LSV tests were performed using Shanghai Chenhua CHI760e electrochemical workstation. The scan rate during CV testing was 50mV s -1 , scan 50 times, voltage range 0.05-1V vs.RHE. Before performing the linear scan test, O needs to be introduced into the electrolyte. 2 Half an hour, scanning speed is 10mV s -1 , scanning range 0.05-1V vs.RHE, wait for O 2 After reaching saturation, the LSV test was performed at a rotation speed of 1600 rpm and the curve was recorded. In order to quantitatively analyze the ORR activity of the catalyst, the kinetic current density at 0.9 V was calculated according to the Koutecky-Levich equation and normalized to the mass loading of Pt, and finally the mass specific activity (MA) of the catalyst was calculated. By accelerated durability test (ADT), at room temperature, in O 2 Saturated 0.1M HClO 4 The structure and electrochemical stability of the catalyst were evaluated by continuous potential cycling in the solution. Specifically, CV was performed in the voltage range of 0.6-1.1 V vs. RHE with a scan rate of 100 mV s -1 , scanning circle number is 10000. And record the CV curve before and after ADT test, LSV curve and MA before and after comparison.
[0041] Figure 4The CV curves, ORR polarization curves, and mass activity and area specific activity of Pt1Co1-IMC / C and the comparative Pt / C catalysts are compared; (a) is the CV curves of Pt1Co1-IMC / C and Pt / C catalysts; (b) is the ORR polarization curves of Pt1Co1-IMC / C and Pt / C catalysts; (c) is the mass activity and specific activity comparison of Pt1Co1-IMC / C and Pt / C catalysts. Obviously, compared with Pt / C catalyst, Pt1Co1-IMC / C showed higher mass activity and area specific activity for ORR, with a mass specific activity of 0.35A mg at 0.9V. Pt -1 , which is about three times that of Pt / C catalyst.
[0042] Figure 5 The cyclic voltammogram (a), polarization curve (b), and changes in mass (c) and area (d) specific activity of the Pt1Co1-IMC / C catalyst before and after 10,000 cycles of the cycle test. It can be seen from the figure that after 10,000 cycles of accelerated testing, the mass specific activity of Pt1Co1-IMC / C decayed by 31%, while the mass specific activity of the Pt / C catalyst under the same conditions decayed by 50%, proving that Pt1Co1-IMC / C has better stability.
[0043] (2) The Pt1Co1-IMC / C catalyst prepared in Example 1 was applied to a fuel cell test. A membrane electrode (MEA) was prepared using a catalyst coated membrane method (CCM). The prepared MEA was installed in a fuel cell test fixture. H was introduced into the anode. 2 , O is introduced into the cathode 2 Or air. The specific test conditions are as follows: temperature 80°C, 100% humidification, back pressure 1 bar, anode load 0.1 mg Pt cm -2 , gas flow rate 0.4slpm, cathode loading 0.2mg Pt cm -2 , gas flow rate 1slpm. Steady-state polarization curve test and stability test were carried out using a fuel cell test system to evaluate the activity and stability of the catalyst in actual application. For comparison, the fuel cell performance of MEA prepared using commercial 20wt% Pt / C was also evaluated under the same test conditions.
[0044] Figure 6 For Pt1Co1-IMC / C and Pt / C in H 2 – Air and H 2 –O 2 Steady-state polarization curves in fuel cells (a, b) and Pt1Co1-IMC / C catalyst in H 2-air conditions (c), and compared with the performance of some published materials (d). Obviously, at low Pt dosage, the highest power density of hydrogen-air fuel cells using Pt1Co1-IMC / C catalyst as cathode reaches 1.06 W cm -2 , while the performance of Pt / C is 0.85 W cm -2 The maximum power density of hydrogen-oxygen fuel cells using Pt1Co1-IMC / C catalyst as cathode is as high as 2.13 W cm -2 Importantly, the mass specific activity of Pt1Co1-IMC / C at the membrane electrode level at 0.9 V is 0.18 A mg Pt -1 , much higher than 0.05A mg of Pt / C catalyst Pt -1 ; The membrane electrode using Pt1Co1-IMC / C has undergone stability testing for more than 100 hours, and the battery voltage remains basically unchanged, proving its high stability.
[0045] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.
Claims
1. A method for preparing a PtCo intermetallic compound, characterized in that: The following steps are involved: 1) Dissolve [Co(NH3)5Cl]Cl2 in water, add carbon powder, disperse by ultrasonication, and stir overnight to obtain solution A; dissolve potassium chloroplatinite in water to obtain solution B; 2) adding the solution B dropwise to the solution A and stirring to react, filtering and drying after the reaction is completed to obtain a precursor mixture; 3) heating the precursor mixture in a reducing atmosphere for 2 h to 6 h at a heating temperature of 600° C. to 900° C., and then naturally cooling to room temperature to obtain a target powder; 4) washing the target powder in an acid solution, washing with water, and drying to obtain the PtCo intermetallic compound.
2. The preparation method according to claim 1, characterized in that: In the step 2), the dropping rate is 2 mL / h-15 mL / h, and the stirring rate is 400 rpm-1200 rpm.
3. The preparation method according to claim 2, characterized in that: In the step 2), after the solution B is added dropwise, stirring is continued for 5 h to 12 h.
4. The preparation method according to claim 1, characterized in that: In the step 2), the molar ratio of potassium chloroplatinite in the solution B to [Co(NH3)5Cl]Cl2 in the solution A is 1:(1-2).
5. The preparation method according to claim 1, characterized in that: In the step 3), the precursor mixture is placed in a reducing atmosphere, and the temperature is raised to 600° C.-900° C. at a heating rate of 5° C. / min-10° C. / min, and maintained for 2 h-6 h.
6. The preparation method according to claim 1, characterized in that: In the step 3), the reducing atmosphere includes hydrogen and argon.
7. The preparation method according to claim 1, characterized in that: In the step 4), the specific process of washing includes: ultrasonically dispersing the target powder in the acid solution, and stirring at 55° C.-85° C. for 4 h-12 h.
8. The preparation method according to claim 1, characterized in that: In the step 1), the ultrasonic time is 0.5h-2h; and / or, in the step 1), the carbon powder is C-72, EC-300, KB-600 or BP-2000; and / or, in the step 2), the drying temperature is 55°C-80°C, and the drying time is 12h-24h; and / or, in the step 4), the drying temperature is 55°C-80°C, and the drying time is 12h-24h; and / or, in the step 4), the acid solution is an aqueous solution of sulfuric acid, nitric acid, hydrochloric acid or perchloric acid, and the concentration of the acid solution is 0.1M-5M.
9. A PtCo intermetallic compound, characterized in that Prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the PtCo intermetallic compound according to claim 9 in the field of fuel cell ORR.
Citation Information
Cited By
Preparation method of ORR reaction catalyst
CN120261608A